2022
DOI: 10.3847/psj/ac562e
|View full text |Cite
|
Sign up to set email alerts
|

Blue Marble, Stagnant Lid: Could Dynamic Topography Avert a Waterworld?

Abstract: Topography on a wet rocky exoplanet could raise land above its sea level. Although land elevation is the product of many complex processes, the large-scale topographic features on any geodynamically active planet are the expression of the convecting mantle beneath the surface. This so-called “dynamic topography” exists regardless of a planet’s tectonic regime or volcanism; its amplitude, with a few assumptions, can be estimated via numerical simulations of convection as a function of the mantle Rayleigh number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 173 publications
(238 reference statements)
0
5
0
Order By: Relevance
“…Previous analyses exploring the gravity arising from Europa's seafloor assumed that seafloor topography is supported by a combination of lithospheric strength and Airy isostasy (Pauer et al 2010;Dombard & Sessa 2019). Here, in order to scale the topographies of these terrestrial bodies, we expand the explored physics to consider topographic support arising from dynamic topography, i.e., supported by convection (Guimond et al 2022). Such convection involves rising hot plumes, which flatten beneath the lid (lithosphere).…”
Section: Terrestrial Body Analogsmentioning
confidence: 99%
“…Previous analyses exploring the gravity arising from Europa's seafloor assumed that seafloor topography is supported by a combination of lithospheric strength and Airy isostasy (Pauer et al 2010;Dombard & Sessa 2019). Here, in order to scale the topographies of these terrestrial bodies, we expand the explored physics to consider topographic support arising from dynamic topography, i.e., supported by convection (Guimond et al 2022). Such convection involves rising hot plumes, which flatten beneath the lid (lithosphere).…”
Section: Terrestrial Body Analogsmentioning
confidence: 99%
“…Constraints on the interior reservoir capacity are covered in this work. Lastly, the potential size of the surface reservoir can be constrained by topography, as was shown in Guimond et al (2022), who found that massive planets should be topographically featureless and thus more liable to complete inundation.…”
Section: Implications For Waterworld Frequencymentioning
confidence: 94%
“…In a planet's atmosphere, water is likely to be both the major greenhouse gas species and source of clouds, critical therefore for climate and atmospheric dynamics (e.g., Pierrehumbert 1995;Frierson et al 2006Frierson et al , 2007. At a planet's surface, the amount of water trades off with topography to determine whether or not continents are exposed (Cowan & Abbot 2014;Höning & Spohn 2016;Guimond et al 2022). In extreme cases, planets with high surface water inventories will be ocean worlds, presenting possible challenges for carbon cycling (Kitzmann et al 2015;Noack et al 2016;Nakayama et al 2019;Höning et al 2019;Krissansen-Totton et al 2021) and prebiotic chemistry (Patel et al 2015;Rimmer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surface evolution driven by plate movements (e.g., Coy 2022) means that all of these factors may constantly coevolve on an Earth-like planet with plate tectonics. Further, planets in the "stagnant lid" mode (no plate tectonics; e.g., Foley 2019) may display systematic differences in topography (Guimond et al 2022) and outgassing rates (Guimond et al 2021), likely introducing further major variation into all of these factors controlling weathering rates and climate evolution. Correlations and feedbacks between the many variables controlling weathering fluxes could significantly change the picture we have presented, and a much broader parameter sweep and investigation of these issues is necessary.…”
Section: Continental Configurationmentioning
confidence: 99%